On the use of indexes derived from photoplethysmographic (PPG) signals for postoperative pain assessment: A narrative review. (February 2023) - Argüello-Prada, Erick J.; Molano Valencia, Rodolfo D.
Abstract: Postoperative pain (POP) occurs following the trauma caused by surgery, and its management depends mostly on timely and accurate assessment. Since traditional POP assessment tools rely on the patient's ability to communicate pain intensity, there is a need for alternative approaches that can be used even when the patient cannot provide the self-report. Some indexes derived from photoplethysmographic (PPG) waveform analysis, such as Surgical Pleth Index (SPI) and Perfusion Index (PI), have shown some promise during surgery. However, their usefulness in postoperative scenarios remains controversial. To provide possible explanations for this issue and a foundation for future research, we examined the current state-of-the-art devoted to exploring the potential value of PPG-derived indexes in POP assessment. After critically reviewing the related literature, we identified several challenges at the conceptual and methodological levels, including an incomplete understanding of the POP experience, an inaccurate interpretation of the results provided by statistical tools, and a lack of validity protocol standards. As PPG-derived indexes could still be valuable for developing objective and valid tools to assess pain after surgery, it is necessary to clarify how those metrics might contribute to POP conceptualization, assessment, and management. The uniqueness of the pain experienced in the post-anesthesia care unit must also be recognized by both researchers and clinicians.